Hurricane disaster - Jones, Lynda (New York : Scholastic, 2011)
Answers such questions as: What is a hurricane? Where does it come from and how does it form? and How do you keep your family safe from a barreling storm?
Alert! Alert! -- Sea monsters -- Air Force -- Storm factory -- Parts of a hurricane -- Blow, wind, blow -- Where's the storm? -- Hurricane hunters -- Underwater -- Historic hurricanes -- Rescue mission -- Tally up -- How to stop a hurricane -- Future forecast.
Includes bibliographical references.
Keywords: Hurricanes -- Juvenile literature; Hurricanes